Geographical patterns of congruence and incongruence between correlative species distribution models and a process-based ecophysiological growth model (JOURNAL OF BIOGEOGRAPHY, 2013)
AimOur aim was to map the climate dependence of tree species distributions (probability of occurrence) and forest growth (net primary productivity) by comparing the congruence and incongruence between correlative and process-based modelling approaches. LocationIberian Peninsula, south-western Europe. MethodsWe used forest inventory data for three widespread tree species (Quercus ilex, Pinus halepensis and Pinus sylvestris) to model climatic suitability with an ensemble of seven correlative species distribution models (using biomod). We then simulated forest net primary productivity (NPP) as a surrogate of forest growth for forests of each species using an ecophysiological process-based model (gotilwa+) along a gradient of climatic suitability. The spatial distribution of the growth estimates was then compared with that of the suitability estimates, and robust regression was used to classify regions in terms of model congruence. ResultsQuercus ilex and P.sylvestris both showed a positive relationship between forest NPP and climatic suitability. The main discrepancies were found in the north of the peninsula, where there was high potential forest growth but low climate suitability. Low forest-growth estimates in areas of high suitability only appeared for P.sylvestris in southern montane regions. Pinus halepensis always showed a negative relationship between estimated growth and climatic suitability. The analysis of other ecophysiological parameters (mean leaf life and leaf area index) suggests that this tree species has different physiological strategies that allow differential growth rates in areas of low suitability. Main conclusionsWe found that the relationship between estimated growth and distribution varies strongly in different areas and species. Mapping the incongruences between the predicted climatic suitability and growth allowed us to identify regions where other factors (e.g. biotic interactions) may be more significant than the physiological limits on growth. We show that new insights into species distributions can be gained from mapping the differences between correlative and process-based models.

The importance of mesophyll conductance in regulating forest ecosystem productivity during drought periods - KEENAN, Trevor; Sabaté, Santi; Gracia, Carlos (Global Change Biology, 2010)
Water availability is the most limiting factor to global plant productivity, yet photosynthetic responses to seasonal drought cycles are poorly understood, with conflicting reports on which limiting process is the most important during drought. We address the problem using a model-data synthesis approach to look at canopy level fluxes, integrating twenty years of half hour data gathered by the FLUXNET network across six Mediterranean sites. The measured canopy level, water and carbon fluxes were used, together with an inverse canopy ecophysiological model, to estimate the bulk canopy conductance, bulk mesophyll conductance, and the canopy scale carbon pools in both the intercellular spaces and at the site of carboxylation in the chloroplasts. Thus the roles of stomatal and mesophyll conductance in the regulation of internal carbon pools and photosynthesis could be separated. A quantitative limitation analysis allowed for the relative seasonal responses of stomatal, mesophyll, and biochemical limitations to be gauged. The concentration of carbon in the chloroplast was shown to be a potentially more reliable estimator of assimilation rates than the intercellular carbon concentration. Both stomatal conductance limitations and mesophyll conductance limitations were observed to regulate the response of photosynthesis to water stress in each of the six species studied. The results suggest that mesophyll conductance could bridge the gap between conflicting reports on plant responses to soil water stress, and that the inclusion of mesophyll conductance in biosphere–atmosphere transfer models may improve their performance, in particular their ability to accurately capture the response of terrestrial vegetation productivity to drought.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: 16 june 2009; conductance limitations; Drought; FLUXNET; june 2009 and accepted; Mediterranean climate; mesophyll conduc-; mesophyll conductance; photosynthesis; received 12 march 2009; revised version received 2; tance; water stress

Growth response of mixed mediterranean oak coppices to rainfall reduction - Cotillas, Miriam; Sabaté, Santi; Gracia, Carlos; Espelta, Josep Mª (Forest Ecology and Management, 2009)
Climate change is one of the major challenges for ecosystem conservation. One of the most vulnerable areas to climate change is the Mediterranean Basin which is expected to suffer important changes in temperature and precipitation in the next few decades, leading to a warmer and dryer climate. Therefore, it is necessary to determine species-speciﬁc responses to increased drought to predict possible future changes in the structure and composition of Mediterranean forests, as well as to identify appropriate management strategies to mitigate these effects. The main aim of this study has been to experimentally simulate the effects of a 15% reduction in annual rainfall on the survival and growth of two co-occurring Mediterranean oaks with contrasting leafhabit (the evergreen Quercus ilex spp. ilex and the winter-deciduous Quercus cerrioides) and, to assess whether traditional selective thinning carried out in these mixed oak coppices (i.e. selection of one to few stems per stump) can modify the consequences of rainfall reduction. Soil moisture decreased under the rainfall reduction level while it increased in the thinned plots. Reduced rainfall did not inﬂuence tree mortality, but did lead to species-speciﬁc effects on height growth: no changes were observed in Q. ilex while height growth rate of Q. cerrioides decreased (c.a. 20%). Selective thinning improved tree growth (c.a. 50%) in stands both under natural and, and to a lesser extent, under reduced rainfall conditions. Nevertheless, the positive effects of thinning rapidly declined during our three years experiment, probably because the vigorous resprouting of thinned stumps. Our results show that the forecasted reduction in annual rainfall for the Western Mediterranean Basin can constrain the growth of some deciduous oaks in mixed oak coppices. Traditional selective thinning can increase soil moisture and encourage tree growth, thus partially mitigating this effect. However, the transient results observed in this experiment suggest the need to reconsider the intensity and the frequency of this traditional management practice in light of new climatic scenarios
Keywords: climate change; Drought; Forest management; Quercus cerrioides; Quercus ilex; resprouting

Growth response of mixed mediterranean oak coppices to rainfall reduction (Forest Ecology and Management, 2009)
Climate change is one of the major challenges for ecosystem conservation. One of the most vulnerable areas to climate change is the Mediterranean Basin which is expected to suffer important changes in temperature and precipitation in the next few decades, leading to a warmer and dryer climate. Therefore, it is necessary to determine species-speciﬁc responses to increased drought to predict possible future changes in the structure and composition of Mediterranean forests, as well as to identify appropriate management strategies to mitigate these effects. The main aim of this study has been to experimentally simulate the effects of a 15% reduction in annual rainfall on the survival and growth of two co-occurring Mediterranean oaks with contrasting leafhabit (the evergreen Quercus ilex spp. ilex and the winter-deciduous Quercus cerrioides) and, to assess whether traditional selective thinning carried out in these mixed oak coppices (i.e. selection of one to few stems per stump) can modify the consequences of rainfall reduction. Soil moisture decreased under the rainfall reduction level while it increased in the thinned plots. Reduced rainfall did not inﬂuence tree mortality, but did lead to species-speciﬁc effects on height growth: no changes were observed in Q. ilex while height growth rate of Q. cerrioides decreased (c.a. 20%). Selective thinning improved tree growth (c.a. 50%) in stands both under natural and, and to a lesser extent, under reduced rainfall conditions. Nevertheless, the positive effects of thinning rapidly declined during our three years experiment, probably because the vigorous resprouting of thinned stumps. Our results show that the forecasted reduction in annual rainfall for the Western Mediterranean Basin can constrain the growth of some deciduous oaks in mixed oak coppices. Traditional selective thinning can increase soil moisture and encourage tree growth, thus partially mitigating this effect. However, the transient results observed in this experiment suggest the need to reconsider the intensity and the frequency of this traditional management practice in light of new climatic scenarios

Seasonality of monoterpene emission potentials in Quercus ilex and Pinus pinea: Implications for regional VOC emissions modeling (Journal of Geophysical Research: Atmospheres, 2009)
VOC emissions from terrestrial ecosystems provide one of the principal controls over oxidative photochemistry in the lower atmosphere and the resulting air pollution. Such atmospheric processes have strong seasonal cycles. Although similar seasonal cycles in VOC emissions from terrestrial ecosystems have been reported, regional emissions inventories generally omit the effect of seasonality on emissions. We compiled measurement data on seasonal variations in monoterpene emissions potentials for two evergreen species (Quercus ilex and Pinus pinea) and used these data to construct two contrasting seasonal response functions for the inclusion in monoterpene emission models. We included these responses in the Niinemets et al. model and compared simulation results to those of the MEGAN model, both with and without its predicted seasonality. The effect of seasonality on regional monoterpene emissions inventories for European Mediterranean forests dominated by these species was tested for both models, using the GOTILWA+ biosphere model platform. The consideration of seasonality in the Niinemets et al. model reduced total estimated annual monoterpene emissions by up to 65% in some regions, with largest reductions at lower latitudes. The MEGAN model demonstrated a much weaker seasonal response than that in the Niinemets et al. model, and did not capture the between species seasonality differences found in this study. Results suggest that previous regional model inventories based on one fixed emission factor likely overestimate regional emissions, and species-specific expressions of seasonality may be necessary. The consideration of seasonality both largely reduces monoterpene emissions estimates, and changes their expected seasonal distribution.

Fine roots dynamics in a Mediterranean forest: effects of drought and stem density (Tree Physiology, 1998)
Summer drought is a characteristic trait of Mediterranean climates and can limit primary production. The holm oak (Quercus ilex L.) forest at the Prades Experimental Complex of Catchments (PECC, NE Spain) was managed by clearcutting until the 1950s. As a result of this practice, the forest has a high density (13000 stems ha−1) that is causing growth stagnation and intense competition for water. A thinning experiment was conducted to release resources, reduce stem competition and improve forest productivity. Minirhizotrons were installed in two plots in each of the thinned and control stands and fine root dynamics quantified to a soil depth of 60 cm over a 2-year period (June 1994–May 1996).Soil water content was higher and soil water penetrated deeper in the soil (30–50 cm) in the thinned plots than in the control plots. In the control plots, soil temperature did not vary substantially with depth (mean = 11.65 °C), whereas soil temperature was higher in shallow horizons compared with deep horizons in the thinned plots. Mean soil temperature was one degree higher in the thinned plots than in the control plots (12.9 versus 11.9 °C). There were always more roots in the top 20 cm of soil in thinned plots than in control plots. In the thinned plots, more than 50% of root density (root no. cm−2) was located in the top 20 cm of soil, whereas root density never reached 50% in the 0–20 cm soil layer of the control plots. Roots longevity varied from 35 to 471 days, and there were significant differences between soil depths. Root longevity was greater in the control plots than in the thinned plots.
10.1093/treephys/18.8-9.601

Canopy structure within a Quercus ilex forested watershed: variations due to location, phenological development, and water availability (Trees-Structure and Function, 1994)
Spatial and temporal changes in canopy structure were studied in 1988 and 1989 in a Mediterranean Q u e r c u s ilex forest in north-eastern Spain. Due to differences in precipitation patterns the 1989 growing season was drier than the 1988 growing season. Sampling was conducted in parallel at two sites which represent endpoints along a slope gradient within a watershed (ridge top at 975 m, and valley bottom at 700 m). At both sites, similar inter-annual changes in canopy structure were observed in response to differences in water availability. Samples harvested in the upper 50 cm of the canopy during 1989 exhibited a de- crease in both average leaf size and the ratio of young to old leaf and stem biomass relative to samples obtained in 1988. At the whole canopy level, a decrease in leaf pro- duction efficiency and an increase in the stem to leaf bio- mass ratio was observed in 1989. Temporal changes in canopy leaf area index (LAI) were not statistically sig- nificant. Average LAI values of Q. ilex at the two sites were not significantly different despite differences in tree stature and density (4.6 m 2 m -2 at the ridge top, and 5.3 m 2 m -2 at the valley bottom). Vertical distribution of leaves and stems within the canopy was very similar at the two locations, with more than 60% of the total LAI in the uppermost metre of the canopy. The possible significance of such an LAI distribution on the canopy carbon budget is discussed.